As relações com a língua estrangeira podem desvelar traços do laço específico com a língua materna?: um estudo de caso de um sujeito poliglota. - Ramos, Gesilda Marques da Silva (2024)
Some theorists, who address issues of the mother language and seek articulation with psychoanalysis, point out that every subject has a specific bond with their mother tongue. This bond will interfere with the learning of new languages, potentially promoting either the capture or resistance to such learning. Our questions regarding the subject's relationship with languages arise from the observation of a learner who spends all their time dedicated to writing in some foreign languages. In this context, we are struck by the unusual places he chooses to write, leading us to inquire about the reasons for this way of dealing with languages. These reflections culminate in the proposal of this thesis, which aims to analyze how the relationship that a self-taught polyglot establishes with foreign languages reveals clues to their specific bond with the mother tongue. In our specific objectives, we propose to: describe the subjective relationship of the subject with FLs; question the meaning of writing for him; identify the place that writing occupies and analyze the meaning and function of each language for the learner. Thus, as a theoretical foundation, we resort to works of Saussurean and Jakobsonian linguistics and Freudian-Lacanian psychoanalysis, emphasizing, among others, the link between the learning of a foreign language and the unconscious desire of the learner. Regarding the methodology, our work refers to a qualitative research, configured as a case study, as it provides the possibility of addressing the subjective relationship of the subject with the language – Bruno, Brazilian, foreign language teacher, and resident in Brazil. As for the instruments used, unstructured interviews were conducted, recorded in audio via WhatsApp, and transcribed in full. As well as, images of the texts written by the research subject. The results of the analyses led us to infer that languages affect him subjectively and "the lack in the mother tongue" (Melman, 1991) leads him to elaborate a psychic work in the midst of languages, as a way of living alterity, as if foreign languages were "his resurrection" (Kristeva, 1994). The specific bond with the mother tongue would guide Bruno's impulses, as he crosses his writings with some sentences in Portuguese, signaling something he cannot shake off. Leading him to have in writing his greatest resource when dealing with the languages he calls adopted. The act of writing takes on unusual features, both because Bruno is compelled to write for much of the day, and because of the places where this writing is done. For beyond papers, he writes on walls, on the floor, on some objects in the house, and has the need to keep these writings from being erased. It is also worth highlighting the intimate nature of much of this writing.